Potret perjuangan mahasiswa dalam cerminan dekad - Riduan Mohamad Nor. (Kuala Lumpur : Jundi Resources, 2007)
Student activities and movements in Malaysia from the 1960s until the present time.
Includes bibliographical references (p. 122-123).
In Malay.
Keywords: Students -- Political activity -- Malaysia; Student movements -- Malaysia